THE ROLE OF INTERNAL WORK ENVIRONMENT DIMENSIONS IN IMPROVING THE QUALITY OF WORK LIFE: A STUDY OF THE OPINIONS OF A SAMPLE OF TEACHING STAFF AT DUHOK POLYTECHNIC UNIVERSITY - Hamdi, Fairooz (Humanities Journal of University of Zakho, 2024)
The current research aims to analyze the relationship between the internal work environment at Duhok Technical University through its physical, social, and organizational dimensions, and the quality of work life. The descriptive analytical method was employed, and the researcher utilized a Google Forms questionnaire to collect data, receiving 57 valid responses from faculty members at both the College of Administrative Technology and the Institute of Administrative Technology. The data were analyzed using a variety of statistical methods relying on the SPSS software (V22). The research yielded several conclusions, the most significant of which include a deficiency in the physical work environment, alongside a positive correlation between the dimensions of the work environment (physical, social, and organizational) and the quality of work life. Moreover, the results affirmed that the organizational dimension has the most significant impact on the quality of work life. Consequently, a set of recommendations were proposed to enhance the internal work environment at the researched university, including: improving facilities and services, enhancing health and safety programs, improving maintenance systems, revising salary and compensation systems, fostering communication between management and faculty members, involving them in decision-making processes, and providing opportunities for professional development.